Treatment of Constipation in Children with Dolichosigma - o’g’li, Durdiyev Sarvarbek Hayitboy (American Journal of Biomedicine and Pharmacy, 2024)
One of the pressing issues in pediatric surgery and pediatric gastroenterology is chronic colonic stasis (CCS) or chronic constipation (CC) CC is defined as a persistent or recurrent condition lasting for more than three months, characterized by a reduction in the age-appropriate frequency of defecation (for children under 3 years of age, fewer than 4–6 bowel movements per week; for children older than 3 years, fewer than 3 bowel movements per week). It is accompanied by difficulty during defecation, a sensation of incomplete bowel emptying, and changes in stool consistency.